2011
DOI: 10.1007/s10943-010-9436-6
|View full text |Cite
|
Sign up to set email alerts
|

The Life of Leaders: An Intensive Health Program for Clergy

Abstract: Clergy suffer from chronic disease rates that are higher than those of non-clergy. Health interventions for clergy are needed, and some exist, although none to date have been described in the literature. Life of Leaders is a clergy health intervention designed with particular attention to the lifestyle and beliefs of United Methodist clergy, directed by Methodist LeBonheur Healthcare Center of Excellence in Faith and Health. It consists of a two-day retreat of a comprehensive executive physical and leadership … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…42 Life of Leaders, a clergy health intervention tailored to United Methodist clergy, has been designed to target multiple aspects of health and health-related leadership, although program outcomes are not yet available. 43 Although one may argue that from a public health perspective, clergy represent a relatively small portion of the US population, clergy have a strong influence on the social and physical environment in their FBOs and serve as role models for health. 17 Many health behavior change theories discuss the importance of social norms, social support, and observational learning as the foundation for effective approaches.…”
Section: An Examination Of Clergy Healthmentioning
confidence: 99%
“…42 Life of Leaders, a clergy health intervention tailored to United Methodist clergy, has been designed to target multiple aspects of health and health-related leadership, although program outcomes are not yet available. 43 Although one may argue that from a public health perspective, clergy represent a relatively small portion of the US population, clergy have a strong influence on the social and physical environment in their FBOs and serve as role models for health. 17 Many health behavior change theories discuss the importance of social norms, social support, and observational learning as the foundation for effective approaches.…”
Section: An Examination Of Clergy Healthmentioning
confidence: 99%
“…Relatively few (13) were engaged in impact evaluation, and even then evaluation findings were not yet available [35]. A large number of the programs utilized a retreat format in which clergy took 2 to 14 days away from work to join with other clergy and health experts to focus on their health [36,37]. The benefit of this retreat format is that it allows clergy to clear their schedule and temporarily attend to their health.…”
Section: Existing Health Interventions For Clergymentioning
confidence: 99%
“…1,2 Aspects of clergy life that may lead to poor health outcomes include relocation, insufficient salary, role expectations (e.g., weekly services, funerals, church management), and lack of privacy. 3 In the 2008/2009 U.S. Congregational Life Survey, clergy reported working on average 46 or more hours a week with 25% reporting secondary employment or leadership of more than one congregation. 4 Studies of clergy have found working longer hours is associated with higher odds of obesity 4 as well as poor mental and physical health outcomes.…”
Section: Purposementioning
confidence: 99%
“…5 The relationship between clergy and spouse has been noted as important in the management of occupational stress 15,16 and engagement of clergy in healthy behaviors. 17 Church traditions, however, create a culture of role expectations, 3 food traditions, 1 and a blurring of lines between clergy, congregation, and family, 8,18 which may make it difficult for clergy to enact healthy behaviors. 19 In addition, most faith-based interventions 20 -22 focus primarily on congregations, leaving a critical gap in our knowledge regarding health interventions for clergy.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation